Medical health care practitioners’ views on collaboration with psychologists in the city of Harare (Zimbabwe) - Pilot Mudhovozi; Simba Mugadza; Levison Maunganidze (Kamla Raj Enterprises (KRE), 2023)
Globally, there has been a realisation that patient health issues are best understood in relation to biological, spiritual, psychological, and social factors rather than viewing illness in purely biological terms. The current study investigated the medical health practitioners’ views on collaboration with psychologists. A descriptive study was conducted. Stratified random sampling was employed to select practitioners from the different areas of specialisation. A questionnaire was used to collect data. The study produced mixed feelings. Although the participants felt that psychologists could be core members of the integrated health team, they however indicated that health institutions did not need psychologists, their patients did not require psychological intervention and they did not refer patients to psychologists. The study recommends that opportunities for collaboration between medical health practitioners and psychologists be explored and implemented at both informal and formal levels for the benefit of the patients.